2021
DOI: 10.3233/bmr-200102
|View full text |Cite
|
Sign up to set email alerts
|

Metal-induced oxidative stress level in patients with fibromyalgia syndrome and its contribution to the severity of the disease: A correlational study

Abstract: BACKGROUND: Fibromyalgia syndrome (FMS) is an extra-articular rheumatological disease characterised by widespread chronic musculoskeletal pain. Metal-induced oxidative stress contributes to the severity of FMS. AIMS: First, this study evaluated the association between plasma levels of toxic heavy metals and essential metals with oxidative stress (OS) markers. Second, the OS markers and metal contents were correlated with the disease severity by assessing the Fibromyalgia Impact Questioner Revised (FIQR) and te… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 27 publications
0
11
0
Order By: Relevance
“…Analysis of blood samples was done at Department of Biochemistry, KGMU. Quantitative determination of zinc and selenium in the serum was done by Inductively Coupled Plasma-Optical Emission Spectrometer (ICP-OES, Optima 8000, Perkin Elmer, USA) [ 34 ]. The level of vitamin D, Vitamin B12 and folate were analyzed in serum by Chemiluminescent Microparticle Immunoassay (CMIA) technology with flexible assay protocol provided by kit ARCHITECT 25-OH VITAMIN D, ARCHITECT B12 and ARCHITECT Folate (Abbot Diagnostics, Iceland) respectively [ 35 37 ].…”
Section: Methodsmentioning
confidence: 99%
“…Analysis of blood samples was done at Department of Biochemistry, KGMU. Quantitative determination of zinc and selenium in the serum was done by Inductively Coupled Plasma-Optical Emission Spectrometer (ICP-OES, Optima 8000, Perkin Elmer, USA) [ 34 ]. The level of vitamin D, Vitamin B12 and folate were analyzed in serum by Chemiluminescent Microparticle Immunoassay (CMIA) technology with flexible assay protocol provided by kit ARCHITECT 25-OH VITAMIN D, ARCHITECT B12 and ARCHITECT Folate (Abbot Diagnostics, Iceland) respectively [ 35 37 ].…”
Section: Methodsmentioning
confidence: 99%
“…Similar data were presented by La Rubia et al, Abdulnasser et al, and Shukla et al, who observed that serum copper, manganese, and aluminum concentration were significantly higher in fibromyalgia patients than in healthy controls. Moreover, the higher concentration of these metals correlated with high FIQR and manifested as increased tender points and pain sensation in FM subjects [ 32 , 63 , 80 ]. Thus, copper and ceruloplasmin may play a role in contributing to the oxidative stress pathogenesis of fibromyalgia.…”
Section: Prooxidative Nutritional Factors In the Development Of Fibro...mentioning
confidence: 99%
“…Moreover, oxidative stress markers also showed negative correlation with zinc and magnesium. 25 In our country, significantly lower serum zinc and magnesium concentrations were determined in FM patients compared to the healthy controls, whereas no significant difference was found for serum selenium concentration. A significant correlation was demonstrated between zinc concentration and the number of tender points, suggesting that these elements might play a role in the pathogenesis of FM.…”
Section: Discussionmentioning
confidence: 58%